2023
DOI: 10.1002/smll.202306116
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mixed Micelles Based on Oppositely Charged Block Copolymers by Machine Learning for Application in Gene Delivery

Katharina Leer,
Liên S. Reichel,
Julian Kimmig
et al.

Abstract: The COVID‐19 mRNA vaccines represent a milestone in developing non‐viral gene carriers, and their success highlights the crucial need for continued research in this field to address further challenges. Polymer‐based delivery systems are particularly promising due to their versatile chemical structure and convenient adaptability, but struggle with the toxicity‐efficiency dilemma. Introducing anionic, hydrophilic, or “stealth” functionalities represents a promising approach to overcome this dilemma in gene deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…It is the best tool for hyperparametric tuning in machine-learning experiments. 128 In order to investigate whether oppositely charged hybrid micelles maintain high transfection efficiency while having excellent cytocompatibility, Leer et al synthesized two sets of oppositely charged double-block terpolymers. 128 The two sets of copolymers contain the same hydrophobic poly( n -butyl acrylate) (PnBA) and hydrophilic 4-acryloylmethane (NAM).…”
Section: Strategies To Improve Gene Transfection Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…It is the best tool for hyperparametric tuning in machine-learning experiments. 128 In order to investigate whether oppositely charged hybrid micelles maintain high transfection efficiency while having excellent cytocompatibility, Leer et al synthesized two sets of oppositely charged double-block terpolymers. 128 The two sets of copolymers contain the same hydrophobic poly( n -butyl acrylate) (PnBA) and hydrophilic 4-acryloylmethane (NAM).…”
Section: Strategies To Improve Gene Transfection Efficiencymentioning
confidence: 99%
“…128 In order to investigate whether oppositely charged hybrid micelles maintain high transfection efficiency while having excellent cytocompatibility, Leer et al synthesized two sets of oppositely charged double-block terpolymers. 128 The two sets of copolymers contain the same hydrophobic poly( n -butyl acrylate) (PnBA) and hydrophilic 4-acryloylmethane (NAM). The charge difference lies in the fact that the cationic copolymer is modified with 3-guanidinoacrylamide (GPAm), and the anionic copolymer is modified with 2-carboxyethylacrylamide (CEAm), which is negatively charged under neutral conditions.…”
Section: Strategies To Improve Gene Transfection Efficiencymentioning
confidence: 99%
“…The assays are based on measuring the increased or decreased fluorescence intensity of EtBr when intercalating with the genetic material or release of genetic material, respectively. 41 To study the ability of the polymer to complex genetic material, an EBA was performed. Therefore, the pKMyc was diluted as described in the polyplexation section with addition of EtBr (1 μg mL −1 ).…”
Section: H Nmr and Sec Plots Of All Polymers)mentioning
confidence: 99%
“…The two sets each consisted of three triblock copolymers with a comparable degree of polymerization (DP) of the hydrophobic block ( H , DP ≈ 80) and either (i) an anionic middle block followed by a cationic outer block or (ii) a cationic middle block followed by an anionic outer block (Table ). Preliminary experiments with block copolymers showed that a molar amount of GPAm greater than 30 mol % and low amounts of CEAm are needed to achieve high transfection efficiencies, using NAM as a “stealth” moiety and for increased colloidal stability . Therefore, the amount of cationic GPAm ( C ) was varied between 30 and 37 mol %, while the amount of anionic CEAm ( A ) ranged from 6 to 14 mol %, which is shown in the bar chart of Figure B.…”
mentioning
confidence: 99%
“…Preliminary experiments with block copolymers showed that a molar amount of GPAm greater than 30 mol % and low amounts of CEAm are needed to achieve high transfection efficiencies, using NAM as a “stealth” moiety and for increased colloidal stability. 41 Therefore, the amount of cationic GPAm ( C ) was varied between 30 and 37 mol %, while the amount of anionic CEAm ( A ) ranged from 6 to 14 mol %, which is shown in the bar chart of Figure 1 B. Numbers after hyphen ( HAC -g/c and HCA -g/c) represent the mol % of GPAm (g) and the mol % of CEAm (c).…”
mentioning
confidence: 99%